Demographic quantification of carbon and nitrogen dynamics associated with root turnover in white clover. (21st February 2018) - Scott, Gavin D.; Baddeley, John A.; Watson, Christine A.; Robinson, David
Abstract: As well as capturing resources, roots lose resources during their lives. We quantified carbon (C) and nitrogen (N) losses associated with root turnover in white clover ( Trifolium repens L.). We grew contrasting cultivars for 18 weeks in soil microcosms. Using repeated in situ observations, destructive sampling, and demographic analysis, we measured changes in C and N concentrations in dry matter of 1st‐ or 2nd‐order (terminal) roots to derive C and N fluxes into and out of root cohorts. C and N fluxes from roots during turnover depended on cohort age and order. Ninety per cent of losses occurred from 2nd‐order cohorts younger than 18 weeks. Losses were greater from roots of the larger, faster growing cultivar Alice than from the smaller lower yielding cultivar S184. C:N ratios of roots and lost material were similar within each order and between cultivars but smaller in 2nd‐ compared with 1st‐order roots. C and N losses during root turnover could be equivalent to at least 6% of aboveground dry matter production in S184 and 12% in Alice at the field scale. C and N losses associated with root turnover will have potentially significant and previously unrecognized impacts on crop productivity, resource dynamics, and long‐term soil fertility. Abstract : We measured the amounts of carbon and nitrogen lost from white clover plants as their roots grew, matured, and died to test if this is an important pathway through which legume crops influence the soil. The equivalent of about one tenth of the crop's annual productivity was lost in this way, most via the turnover of the finest terminal members of the root system. This work suggests that genetic variation in root turnover could be exploited to better manipulate soil fertility and potential carbon sequestration in clover‐rich pastures.